The Disruption of the 1940 and 2020 Tokyo Olympics: Sports Diplomacy During War and Pandemic - Md Akhir, Md Nasrudin; Govindasamy, Geetha; Paidi, Rohayati (WILAYAH: The International Journal of East Asian Studies, 2021)
Sports diplomacy possesses the power to bring the best of the human spirit by affirming shared aspirations. Olympic Games share a similar propensity to bring people together across boundaries regardless of race, nationality, religion, income and country, reinforcing the true basis of sportsmanship and solidarity between all nations and spectators. The Tokyo Olympics, which were originally scheduled to take place in Japan in 1940, was cancelled due to the outbreak of World War Two. Likewise, the 2020 Olympic Games was postponed to 2021 due to the COVID-19 pandemic. While 80 years ago, amidst the war, Japan faced backlash before it cancelled the Olympic Games, the effect of the re-scheduled 2020 Olympics due to the COVID-19 pandemic demonstrates that such confrontational attitude has been replaced by understanding and solidarity from the global community of the consequences of hosting the games. Using a qualitative method, this article explores the differences in perceptions towards Japan during the 1940s which was overshadowed by war and the year 2020 which continues to be blanketed by the COVID-19 pandemic.